2020
DOI: 10.1186/s12986-020-00473-9
|View full text |Cite
|
Sign up to set email alerts
|

The polyphenol-rich extract from chokeberry (Aronia melanocarpa L.) modulates gut microbiota and improves lipid metabolism in diet-induced obese rats

Abstract: The gut microbiota plays a critical role in obesity and lipid metabolism disorder. Chokeberry (Aronia melanocarpa L.) are rich in polyphenols with various physiological and pharmacological activities. We determined serum physiological parameters and fecal microbial components by using related kits, liquid chromatography-mass spectrometry (LC-MS) and 16S rRNA gene sequencing every 10 days. Real-time PCR analysis was used to measure gene expression of bile acids (BAs) and lipid metabolism in liver and adipose ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Bioactive compounds of AR include neochlorogenic and chlorogenic acid, anthocyanins, flavanols, flavonols [16]. Zhu et al [17] reported that polyphenol-rich AR extract modulated the gut microbiota and improved lipid metabolism in an obese rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds of AR include neochlorogenic and chlorogenic acid, anthocyanins, flavanols, flavonols [16]. Zhu et al [17] reported that polyphenol-rich AR extract modulated the gut microbiota and improved lipid metabolism in an obese rat model.…”
Section: Introductionmentioning
confidence: 99%
“…β-glucan is one of the prebiotics that decreases serum glucose concentration with increasing propionate and butyrate-producing bacteria in the gut [ 41 ]. Anthocyanins like Aronia and black currant also promote glucose metabolism by increasing the relative abundance of Bacteroides , Prevotella , and Akkermansia to increase butyrate production [ 13 , 42 , 43 ]. Therefore, AGM intake might promote gut microbiota composition contributing to improving glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory quotient was also found to be lowered due to fatty acid transport from white adipose tissue into the mitochondria and subsequent β-oxidation in muscles and liver, determined by increased expression and phosphorylation of the enzymes involved in lipid catabolism such as acyl-CoA synthetase, carnitine acylcarnitine translocase, and carnitine palmitoyl transferase 1 [71]. Similarly, another study reported that 1000 mg of chokeberry polyphenols extract/kg improved dyslipidemia and lipid metabolism and lipogenesis mediated through the FXR and TGR-5 signaling pathway on high fat diet-fed rats [72]. Furthermore, 100 mg/kg cinnamon polyphenol extracts have been found to decrease body weight and visceral fat as well as improve lipid profile and MDA concentrations via the PPAR-α and Nrf2 pathways in rats fed a high fat diet [73].…”
Section: Obesitymentioning
confidence: 98%